Preaching Voxels: An Alternative Approach to Mixed Reality - Regenbrecht, Holger; Park, Jung-Woo (Noel); Ott, Claudia; Mills, Steven; Cook, Matthew; Langlotz, Tobias (Frontiers in ICT, 2019)
For mixed reality applications, where reality and virtual reality are spatially merged and aligned in interactive real-time, we propose a pure voxel representation as a rendering and interaction method of choice. We show that voxels— gap-less volumetric pixels in a regular grid in space— allow for an actual user experience of a mixed reality environment, for a seamless blending of virtual and real, and for a sense of presence and co-presence in such an environment. If everything is based on voxels, even if coarse, visual coherence is achieved inherently. We argue the case for voxels by (1) conceptually defining and illustrating voxel-based mixed reality, (2) describing the computational feasibility, (3) presenting a fully functioning, low resolution prototype, (4) empirically exploring the user experience, and finally (5) discussing current work and future directions for voxel-based mixed reality. This work is not the first that utilises voxels for mixed reality, but is the first that has an holistic view on voxel-based mixed realities as an effective way of experiencing and interacting with mixed reality environments.